Law Enforcement for the Crime of Embezzlement and Customers in Banking Crimes (Study on Police North Sumatra Region) - Purba, Jeni Indriani; Maswandi, Maswandi; Zulyadi, Rizkan (Universitas Medan Area, 2023)
Banking crimes are increasingly developing their modus operandi, especially in the section on embezzlement of customer funds, especially with technological advances, so in law enforcement a more systematic or integrated device is needed that is carried out consistently from various existing law enforcement factors. The formulation of the problem in this study is how to regulate criminal acts of embezzlement of customer funds in banking activities, how the modus operandi of criminal acts of embezzlement of customer funds in banking crimes and its legal consequences and how the North Sumatra Police enforce the law on criminal acts of embezzlement of customer funds in banking crimes. The research method is normative juridical and the methods used in analyzing the data are qualitative and descriptive methods. The results of the research and discussion in this thesis, law enforcement of criminal acts of embezzlement of customer funds in banking crimes is not the same as general criminal enforcement, but uses lex specialis degorat generalis and usesspecial laws. The stages of the investigation carried out include arrest, detention, embezzlement, confiscation, summons, filing.